2018
DOI: 10.1021/acs.inorgchem.8b01650
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Near-Zero Thermal Expansion in REAgxGa4–x (RE = La–Nd, Sm, Eu, and Yb) Induced by Structural Reorganization

Abstract: In this work, we have discovered the anisotropic near Zero Thermal Expansion (NZTE)_ behavior in a family of compounds REAgxGa4-x (RE = LaNd , Sm, Eu and Yb). The compouds adopts CeAl2Ga2 structure type. were obtained as single crystals in high yield by metal flux growth technique using gallium as active flux. Synthesized compounds with space group I4/mmm. Temperature dependent single crystal X-ray diffraction suggests that all the compounds exhibit zero thermal expansion along c direction in the temperature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…They exhibit numerous structural properties [1][2]. There is a focus on structural, electronic, magnetic, and thermodynamic properties, such as fermionic, heavy-fermions [3][4], and half-metallic behavior in rare-earth intermetallic compounds such as SmInZn, SmInCd and SmTlZn [5][6], and the giant magneto-resistance device is an industrial application of heavy rare earth compounds [7][8][9]. These equal-atomic type compounds of rare earth have been investigated seriously in the last few years [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit numerous structural properties [1][2]. There is a focus on structural, electronic, magnetic, and thermodynamic properties, such as fermionic, heavy-fermions [3][4], and half-metallic behavior in rare-earth intermetallic compounds such as SmInZn, SmInCd and SmTlZn [5][6], and the giant magneto-resistance device is an industrial application of heavy rare earth compounds [7][8][9]. These equal-atomic type compounds of rare earth have been investigated seriously in the last few years [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Intermetallic compounds with the composition RETX 3 (RE -Rare Earth, T -Transition metals, X -Group 13-15 elements, except non-metals) have been studied extensively because of their structural diversity, [1,2] which leads to interesting physical properties. [3][4][5] The presence of 4f electrons in RE and the d-electrons in T and their interaction favors the generation of interesting magnetic and electronic properties such as ferromagnetism, antiferromagnetism, [6][7][8][9][10] spin-glass, [11] Kondo behavior, [8,12,13] heavy fermion behavior, [14,15] mixed valence, [16][17][18] and superconductivity. [7,[19][20][21][22][23][24] Along with physical properties some solid-state structural transformation, [18] narrow band gap semiconductor [16] The highly localized 4f electrons in rareearth atoms in "many" intermetallic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the long-range ferromagnetic ordering is favored at lower Ga concentrations. [29] Apart from the fundamental studies rareearth based intermetallics has found their industrial applications in cryogenic magnetic refrigeration, [30,31] magnetic applications, [32] catalysis, [33][34][35][36] thermal spray coating, [37] zero thermal expansion [3,38,39] and many more.…”
Section: Introductionmentioning
confidence: 99%